Membangun Soft Skill Siswa SMK melalui Pelatihan Optimalisasi Pengelolaan Media Sosial Konten Pemasaran - Nofriska Krissanya; Dewi Agustin Pratama Sari; Sholikhah; Ika Febrilia; Agung Kresnamurti Rivai Prabumenang; Andi Muhammad Sadat; Ryna Parlina; Raihanisa Dara Dhinanty (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
The rapid development of technology has a significant impact on human resources. Not only does it simplify and help, but it also forces human resources to have highly competitive power. In addition, developing a guaranteed world shifts the market from traditional to more digital. In the current digital era, marketing expertise in managing social media is essential. It also aligns with the needs explored by teachers at Vocational High Schools (SMK) in Jakarta, where students must be equipped with special skills to be a competitive attraction when continuing their education or entering the professional world. Therefore, social media optimization and content creation training was provided to SMK students in Jakarta. This training is hoped to open up insights and improve students' soft skills related to social media management optimization and content marketing creation.